PROMOSI KESEHATAN TERKAIT IMUNISASI DASAR DALAM RANGKA MENINGKATKAN PEMANFAATAN PELAYANAN IMUNISASI ANAK PADA MASA PANDEMI - Warnaini, Cut; Nurbaiti, Lina; Buana, Belva Bhadranitya (Universitas Mataram, 2024)
The COVID-19 pandemic has caused various aspects of life in the world to experience quite drastic changes, especially health aspects. Studies show that there has been a decrease in the number of immunization services in health facilities by 84% as a result of the pandemic and the Large-Scale Social Restrictions (PSBB) policy implemented by the government. In many countries, low immunization coverage can be caused by several factors, including geographic barriers that cause disparities between urban and rural areas. A study found much lower vaccination rates in children living in rural areas compared to urban areas. This inequality in vaccine coverage rates can be overcome, one of the ways is by increasing knowledge about vaccines. This activity aims to increase community capacity regarding basic immunization programs during the pandemic. It is hoped that the results of this activity can act as a basis for consideration for regional and national policy making regarding health promotion and education in order to increase community capacity in the context of basic immunization programs. The outreach activity was held at the Narmada Community Health Center, West Lombok Regency in September 2021. Participants in the activity were the local community consisting of mothers of productive age who were either pregnant or planning to become pregnant, midwives and local community leaders. However, due to the second wave of COVID-19, the activity mechanism was facilitated through digital media. The enthusiasm of the activity participants was so good that the number of participants exceeded the initial target. Activity participants watched educational videos and were able to master the material presented well. This is proven by an increase in the post test scores obtained by participants compared to the pre test scores. Apart from that, through this activity five educational video episodes were produced with various themes related to basic immunization during the pandemic which were distributed via the YouTube channel. The activity succeeded in increasing community capacity regarding basic immunization programs during the pandemic. This will be the basis for the team's consideration in making recommendations for regional and national policies regarding health promotion and education in order to increase community capacity in the context of basic immunization programs.